The progress and perspective of electrospun carbon nanofibers based anode materials for potassium ion storage: A mini review - Ming Xiao; Ruixue Li; Ting Yang; Yu Dai (Frontiers in Energy Research, 2022)
Potassium ion battery (PIB) is one of the promising substitutes for lithium ion battery. Developing new anode materials is still one of the key factors to promote the electrochemical performances of PIB. Electrospun carbon nanofibers based binder-free electrodes have received widely researches because multi-advantages of good conductivity, large surface areas and structural stability. In this review, the latest research progress in enhancing the potassium ion storage properties based on electrospun carbon nanofibers through introducing porous structure, doping heteroatoms and preparing composites have been summarized. The effects of pore structure, heteroatom types and non-metal/metal loading on specific surface area, conductivity, lattice distance and potassium storage performance of the electrospun carbon nanofiber electrode were emphatically discussed. In addition, several suggestions for industrial application of electrospun carbon nanofiber electrodes for potassium ion storage were proposed in this review.